Design and Development of a Fire Monitoring and Alert System Prototype Based on the Internet of Things (IoT) - Ramadika Dimas Nugroho; Saludin Muis (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Bekasi City experienced a significant increase in fire incidents in 2023, reaching 446 cases with material losses amounting to IDR 132.2 billion. Fires are generally only detected when the fire has already spread or the smoke has been extinguished, increasing the risk of losses. To address this, this study designed a prototype Internet of Things (IoT)-based fire monitoring and warning system in the Zedigit program and media team's workspace using a prototype method. The system uses one master module and three child modules equipped with a KY-026 fire sensor, an MQ-2 smoke sensor, and a DHT22 temperature sensor. Sensor data is sent to the master module via the MQTT protocol using a NodeMCU ESP8266. When a fire hazard is detected, the system activates a buzzer and sends a notification via the Telegram app in real time. This system is expected to provide fast and accurate early fire warnings, reducing the risk of asset damage and improving employee safety. This system is an effective solution for improving fire safety management within the Zedigit environment through digital technology.